Analysis of Organizational Culture Based on The Organizational Culture Assessment Instrument (OCAI) - Mumtazah, Humaira; Kadiyono, Anissa Lestari; Ashriyana, Rezki (Universitas Mercu Buana, 2024)
The research aims to determine the current and expected culture at the Tasikmalaya City Institute. The research method used is descriptive quantitative, examining organizational culture variables. The instrument used is the OCAI (Organizational Culture Assessment Instrument) measuring instrument, which has been translated. Participants were 31 lecturers and staff. The findings of this research are that the culture currently occurring is a close clan culture characterized by high levels of kinship, collaboration, and prioritizing flexibility, commitment, and cooperation. Meanwhile, the culture expected to occur in the future is a hierarchical culture characterized by a more structured culture, having a formalized system, prioritizing strict, stable, consistent, and efficient control. The Institute can consider taking cultural change intervention steps to address these gaps.